The Meaning of the Javanese Proverb "Alon-Alon Waton Kelakon" Toward Mindfulness Practices in Daily Life - Ani Supriyani; Hastangka Hastangka (Journal of Social Research, 2025)
This study aims to explore the meaning of the Javanese proverb Alon-Alon Waton Kelakon through the lens of indigenous psychology, and how this pitutur luhur (cultural wisdom) is internalized and practiced as a form of eling lan waspada (mindfulness) in the daily lives of the Javanese people. The proverb reflects time-tested local wisdom, emphasizing sabar (patience), tata titi (perseverance), and full presence in life’s processes. Using a qualitative phenomenological approach, this research investigates the lived experiences of individuals who consciously embody this principle. The findings reveal that Alon-Alon Waton Kelakon is not merely about moving slowly but represents a culturally embedded laku urip (life strategy) that aligns with the spiritual (spiritualitas), ecological (lingkungan), and communal (guyub rukun) dimensions of Javanese society. It reflects a contextual form of mindfulness—spiritually rooted and harmoniously integrated with nilai budaya (cultural values) and keseimbangan batin (inner balance). Thus, this study affirms that mindfulness, when grounded in local traditions, can serve as a genuine form of indigenous psychology rooted in collective identity and cultural wisdom.